The girl i used to be eaudiobook - Henry, April (Tantor Media, 2017)
When Olivia's mother was killed, everyone suspected her father of murder. But his whereabouts remained a mystery. Fast forward fourteen years. New evidence now proves Olivia's father was actually murdered on the same fateful day her mother died. That means there's a killer still at large. It's up to Olivia to uncover who that may be. But can she do that before the killer tracks her down first?